2014
DOI: 10.31729/jnma.2707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gender and Body Weight on Postprandial Glucose and Lipid Metabolism in Adults with Type 2 Diabetes

Abstract: Introduction: The magnitude of the healthcare problem of type-2-diabetes increases according to its association with several risk factors for cardiovascular diseases such as obesity and dyslipidemia. Methods: This study took place in the north-western region of Algeria. We aimed to assess the effect of body weight and gender on postprandial lipid and glucose in type-2-diabetes patients. 93 diabetic patients (age 55.65±13.81 years) were studied. Anthropometric parameters and body mass index (BMI) were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…However, the current study found fewer risk factors in the study population of Tibetans in China. In previous studies, age, obesity, hypertension, TC levels, TG levels, living in low-income areas, alcohol consumption were confirmed as risk factors for DM at sea level (11)(12)(13)(14). With regard to age, FPG levels increase with age, with a 0.07-mmol/L increase in as a risk factor FPG levels each decade of life (11).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, the current study found fewer risk factors in the study population of Tibetans in China. In previous studies, age, obesity, hypertension, TC levels, TG levels, living in low-income areas, alcohol consumption were confirmed as risk factors for DM at sea level (11)(12)(13)(14). With regard to age, FPG levels increase with age, with a 0.07-mmol/L increase in as a risk factor FPG levels each decade of life (11).…”
Section: Discussionmentioning
confidence: 74%
“…In addition, a study reported that median FPG level was 81.6 mg/dL for men living above 3,000 m and was significantly higher than that in non-pregnant adult women, who had a median FPG level of 71.7 mg/dL ( 19 ); thus, there are also sex differences in FPG levels at this altitude. Moreover, sex was closely related to the postprandial glucose response in patients with T2 DM in low-altitude ( 14 ). Thus, the relationship between sex and FPG in the present study is consistent with findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Given that serum lipid may be affected by sex, age and BMI level,27–29 we examined the associations between serum lipid and pterygium stratified by these three variables. As shown in table 4, among participants aged 40–49 years, each 1 mmol/L increase in HDL-C and LDL-C was associated with 72% higher (OR: 1.72, 95% CI: 1.21 to 2.44) and 26% higher (OR: 1.26, 95% CI: 1.06 to 1.48) risk of pterygium, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Parameters with p value <0.05 in the univariable analyses and other established risk factors for pterygium were adjusted in the models, and backward-conditional pattern was applied to filter the meaningful risk factors. To evaluate whether these relationships differ by pterygium risk factors, we did a subgroup analysis stratified by sex, age and BMI status those have been demonstrated to be involved in serum lipid 27–29. Heterogeneity across subgroups was assessed using the likelihood ratio test, comparing the difference in fit statistics between models with a cross-product term of serum lipid and subgroup variable and those without that term.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes manifests differently in male and female patients for various parameters including post-prandial glucose levels ( Diaf et al, 2014 ), glucose tolerance ( Mauvais-Jarvis, 2017 ), and insulin secretion and action ( Basu et al, 2017 ). Some of these differences were also found in euglycemic, non-obese subjects ( Chan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%